The functional maturity of grafted human pluripotent stem cell derived-islets (hSC-Islets) evaluated by the glycemic set point during blood glucose normalizing process in diabetic mice - Shigeharu G. Yabe; Satsuki Fukuda; Junko Nishida; Fujie Takeda; Hitoshi Okochi (Heliyon, 2023)
Human pluripotent stem cell (hPSCs) derived-pancreatic islets (hSC-islets) are good candidates for cell replacement therapy for patients with diabetes as substitutes for deceased donor-derived islets, because they are pluripotent and have infinite proliferation potential. Grafted hSC-islets ameliorate hyperglycemia in diabetic mice; however, several weeks are needed to normalize the hyperglycemia. These data suggest hSC-islets require maturation, but their maturation process in vivo is not yet fully understood. In this study, we utilized two kinds of streptozotocin (STZ)-induced diabetes model mice by changing the administration timing in order to examine the time course of maturation of hSC-islets and the effects of hyperglycemia on their maturation. We found no hyperglycemia in immune-compromised mice when hSC-islets had been transplanted under their kidney capsules in advance, and STZ was administered 4 weeks after transplantation. Of note, the blood glucose levels of those mice were stably maintained under 100 mg/dl 10 weeks after transplantation; this is lower than the mouse glycemic set point (120–150 mg/dl), suggesting that hSC-islets control blood glucose levels to the human glycemic set point. We confirmed that gene expression of maturation markers of pancreatic beta cells tended to upregulate during 4 weeks after transplantation. Periodical histological analysis revealed that revascularization was observed as early as 1 week after transplantation, but reinnervation in the grafted hSC-islets was not detected at all, even 15 weeks after transplantation. In conclusion, our hSC-islets need at least 4 weeks to mature, and the human glycemic set point is a good index for evaluating ultimate maturity for hSC-islets in vivo.